Mobile Health Campaigns and Changes in Clean and Healthy Living Behavior (PHBS) in the Community - hasnidar, hasnidar; Lidiyawati, Herlina; mustar, Mustar (Oshada, 2025)
Changes in clean and healthy living behavior (PHBS) are an important component in improving public health. However, conventional outreach often faces limitations in reaching the community broadly and sustainably. This study aims to analyze the effect of mobile-based health campaigns (mobile health or mHealth) on changes in PHBS behavior in urban and semi-urban communities. This study used a quantitative approach with a descriptive-correlational design. Data were collected through an online survey of 385 respondents aged 18–50 years in Depok City and Sleman Regency, using a Likert-scale questionnaire. Data analysis was performed using the Pearson correlation test and simple linear regression. The results showed a positive and significant relationship between exposure to mHealth campaigns and PHBS behavior, with the highest correlation values for content quality (r = 0.47) and total exposure score (r = 0.521; p < 0.001). Linear regression showed that mHealth explained 27.1% of the variation in PHBS behavior (R² = 0.271) with a coefficient of b = 0.513. In conclusion, high-quality, relevant, and consistent mHealth campaigns play a crucial role in driving change in healthy, clean, and healthy lifestyle behaviors. Health promotion strategies in the digital era need to integrate these approaches in an adaptive and evidence-based manner.